Colombia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Colombia's outlook is favorable as continued efforts to advance the structural reforms will foster economic diversification and productivity growth. In 2017, adequate policy management brought Colombia near completion of its adjustment to large external shocks while further advancing inclusive growth. Economic growth moderated as private investment and consumption weakened in line with lower national income. Economic growth is expected to rebound strongly in 2018 and further over the medium-term, led by strengthening investment and exports. The combined impact of the structural tax reform, a brighter outlook for oil prices and the authorities Fourth Generation infrastructure agenda will underpin investment while reducing Colombia's relatively large infrastructure gap.